Metastatic Myxofibrosarcoma with Durable Response to Temozolomide Followed by Atezolizumab: A Case Report. (8th March 2021) - Lambden, Jason P.; Kelsten, Max F.; Schulte, Brian C.; Abbinanti, Susan; Hayes, John P.; Villaflor, Victoria; Agulnik, Mark
Abstract: : Myxofibrosarcoma (MFS) is a well-recognized histotype of soft tissue sarcomas that generally presents with localized disease. Herein, we describe the case of a patient with metastatic MFS who experienced durable response to sixth-line therapy with temozolomide. Upon further progression, his tumor was notable for a high tumor mutational burden, and he was subsequently treated with seventh-line immunotherapy, atezolizumab, achieving a second durable response. This case highlights the role of immunotherapy after administration of alkylating agents. Review of the literature indicates that recurrent tumors treated with alkylating agents often experience hypermutation as a means of developing resistance and that checkpoint inhibitors are subsequently effective in these tumors. Key Points: To the authors' knowledge, this is the first report of a patient with myxofibrosarcoma with high tumor mutational burden after administration of temozolomide monotherapy. Hypermutation may be a resistance mechanism for patients with soft tissue sarcoma who develop resistance to alkylating agents. Checkpoint inhibition may be effective therapy in patients with soft tissue sarcoma with high tumor mutational burden as a consequence of alternate systemic therapy resistance. Abstract : This case report highlights the role of immunotherapy after administration of alkylating agents, reporting the first known case of a patient with myxofibrosarcoma who developed high tumor mutational burden after temozolomide monotherapy.